Neuroprotective Effects of Estrogen Through BDNF-Transient Receptor Potential Channels 6 Signaling Pathway in the Hippocampus in a Rat Model of Perimenopausal Depression - Song, Qiaoli; Huang, Weiming; Ye, Wenbin; Yan, Huan; Wang, Liting; Yang, Yan; Cheng, Xi; Zhang, Weiqiang; Zheng, Jie; He, Ping; He, Yaojuan; Fang, Dajun; et al. (Frontiers in Aging Neuroscience, 2022)
Estradiol (E2) has been proven to be effective in treating perimenopausal depression (PD); however, the downstream signaling pathways have not been fully elucidated. TRPC6 plays a vital role in promoting neuronal development and formation of excitatory synapses. Presently, we found that the serum levels of E2 and BDNF declined significantly in the women with perimenopausal depression compared to perimenopausal women, which was accompanied by a clear reduction in TRPC6 levels. To further reveal the effects of TRPC6 on neuronal survival and excitability, the PD-like rat model was established by the total removal of left ovary and 80% removal of right ovary followed by 21 days of the chronic unpredictable mild stress. Intragastric administration of E2 (2 mg/kg), intraperitoneal injection of BDNF/TrB signaling pathway inhibitor (K252a, 100 μg/kg) and TRPC6 agonist (OAG, 0.6 mg/kg), intracerebroventricular infusion of anti-BDNF antibody for blocking BDNF (0.5 μg /24 μl/rat) daily for 21 days were conducted. The levels of BDNF and TRPC6 in rat serum were lower in PD rats compared to the control rats; the depression-like behavior was induced, the neuronal death rate in the hippocampus increased; the thickness of postsynaptic density (PSD) and the number of asymmetric synapses decreased significantly in the PD group. E2 treatment greatly upregulated the serum levels of BDNF and TRPC6, the neuronal excitability indicated by an elevation in the PSD thickness and the numbers of asymmetric synapses, these actions were reversed by K252a; co-administration of TRPC6 agonist and K252a improved neuronal degeneration and increased the neuronal excitability induced in the E2-treated PD rats. K252a or anti-BDNF antibody inhibited the increased neuronal BDNF and TRPC6 expression in E2-treated PD rats; co-treatment of TRPC6 agonist and anti-BDNF antibody reduced neuronal death and increased the BDNF and TRPC6 expression in the hippocampal CA1 neurons in the E2-treated PD rats. These results suggest that the neuroprotective role of E2 in PD is closely related to enhance the activity of BDNF/TRPC6 pathway and is helpful to provide new prevention and strategies.